2021
DOI: 10.1029/2020gl091191
|View full text |Cite
|
Sign up to set email alerts
|

Deadly Heat Stress to Become Commonplace Across South Asia Already at 1.5°C of Global Warming

Abstract: South Asia (SA) is one of those hotspots where earliest exposure to deadly wet‐bulb temperatures (Tw >35°C) is projected in warmer future climates. Here we find that even today parts of SA experience the upper limits of labor productivity (Tw >32°C) or human survivability (Tw >35°C), indicating that previous estimates for future exposure to Tw‐based extremes may be conservative. Our results show that at 2°C global warming above pre‐industrial levels, the per person exposure approximately increases by 2.2 (2.7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 58 publications
5
37
0
Order By: Relevance
“…5f ). Similar arguments could be made based on other risk assessments for India, where potentially deadly heat stress could become commonplace above 1.5 °C 35 .…”
Section: From Local To Global Risk Aggregationsupporting
confidence: 55%
“…5f ). Similar arguments could be made based on other risk assessments for India, where potentially deadly heat stress could become commonplace above 1.5 °C 35 .…”
Section: From Local To Global Risk Aggregationsupporting
confidence: 55%
“…Saeed et al. (2021) found that the population growth would further increase with an exposure factor of ∼2 by the mid‐21st century relative to the base period. They also reported that most SA regions have already experienced such heat stress events with a larger geographical extent and are anticipated to become more hotspots even at the 1.5°C warming target.…”
Section: Discussionmentioning
confidence: 99%
“…In high humidity and temperatures, outdoor workers must slow work, hydrate, and take breaks in the shade to allow the body to cool off and maintain a safe internal body temperature or risk injury, illness, or death if they continue to work at high exertion levels 2 , 4 7 . Workers in many low-latitude locations already experience heat exposure that makes physical labor unsafe 1 , 8 10 . Labor productivity losses associated with reductions in work rate due to heat exposure can be as high as ~280–311 billion $US per year 11 , 12 , most of which are due to losses in low- and middle-income countries in heavy manual labor, such as agriculture and construction 11 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%